Psychological Alienation and its Relationship to Psychological Security among a master's Students at Taif University - Alazmi, Samirah Ghafil (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the feelings of psychological alienation among master's students at Taif University and identify the levels of such feelings. The study also aimed to identify the relationship between the level of psychological alienation and psychological security among the students. The study followed the descriptive approach; where the study sample consisted of (60) master's students at Taif University in Saudi Arabia. The study tool consisted of two measures; the psychological alienation and psychological security measures. The study came out with a set of results, the most important of which were: The total score of responses to the dimension of social isolation was 60.8%. The total score of responses to the dimension of anomie was 54.4%. The total score of responses to the dimension of nihilism was 60.8%. The total score of responses to the dimension of the feeling of impotence reached 45%. The total score of responses to the dimension of reification was 40.5%. The sample's assessment levels on the dimensions of life satisfaction ranged between 36-77.7%; where the total score of responses to this dimension was 71.7%. The total score of responses to the dimension of social appreciation was 59.6%. The total score of responses to the dimension of social stability reached 56%. In addition, the study found a negative relationship of statistical significance between the level of psychological alienation and psychological security among master's students at Taif University according to the correlation coefficient (0.633). In light of the previous results, the study recommended creating a climate in the university that satisfies the needs of the students; keeping them away from feeling alienated, and the need for psychological counselors to be present to provide psychological guidance to students at the university.
Keywords: Psychological Alienation; Psychological Security; Master's Students; Taif University; Saudi Arabia